Governing insecurity in Japan the domestic discourse and policy response - Vosse, Wilhelm; Drifte, Reinhard (Sheffield Centre for Japanese studies/Routledge series, 2014)
"Since the end of the Cold War, Japan's security environment has changed significantly. On the global stage, while the United States is still Japan's most important security partner, the nature of the partnership has changed as a result of shifting demands from the United States, new international challenges such as the North Korean nuclear program and the rise of China. Moreover, Japan has been confronted with new, 'non-traditional' security threats such as international terrorism, the spread of infectious diseases, and global environmental threats. On the domestic level, demographic change, neo-liberal economic reforms and globalization all pose a challenge to the sustainability of the current Japanese lifestyle and have led to a heightened sense of insecurity among many Japanese. Focusing on the domestic Japanese discourse on security, this book expands the standard discussions on security that mostly focus on military security and security in international relations to include perspectives from domestic security, economic and livelihood security as well as sociological discussions of risk and risk management. The chapters cover issues such as Japan's growing perception of regional and global insecurity, the changing role of military force; the perceived risk of Chinese foreign investment; societal, cultural and labour insecurity and how it is affected by demographic changes and migration; as well as food insecurity and its challenges on health and public policy. In turn, each chapter asks how the Japanese public perceives these insecurities; how these perceptions influence the public discourse; who the main stakeholders of this discourse are; and how this affects state-society relations and decision on government policy in Japan. Governing Insecurity in Japan provides new insights into Japanese and international discourses on security, as well as the ways in which security is conceptualized in Japan. As such, it will be of huge interest to students and scholars working on Japanese politics, security studies and international relations."